Pemberdayaan “Generasi Millennial Anti Stunting” (GenMAS) Melalui Pendampingan Pada Remaja Putri Di Kecamatan Gianyar, Kabupaten Gianyar Tahun 2020 - Padmiari, Ida Ayu Eka; Sri Sugiani, Pande Putu; Ariati, Ni Nengah (Poltekkes Kemenkes Denpasar, 2023)
Indonesia is a country that is ranked 17th among 117 countries with nutritional problems with stunting, wasting and overweight (Kemenkes RI, 2016). Based on data from Basic Health Research (Riskesdas) in 2013, the prevalence of stunting in adolescents 16-18 years is 31.4% (7.5% very short and 23.9% short) (Health Research and Development Agency, 2013) and the results of monitoring status Nutrition (PSG) 2017 was obtained nationally by 37% stunting (6.6% very short and 30.4% short) and Bali Province 20.7% (1.5% very short and 19.2% short) (Directorate Public Nutrition, 2017).Based on the situation analysis that has been described, the identification of problems is made as follows: Measurement of anemia in adolescent girls in Sukawati sub-district found that from 50 targets examined, 14 targets (28%) were anemia and 36 targets (72%) were not anemia, Measurement of KEK in adolescents women in Sukawati sub-district found that out of 50 targets examined, 17 targets (34%) experienced KEK and 33 targets (66%) did not experience KEK and the level of knowledge about anemia and KEK most of the young women had less knowledge about anemia and KEK, namely 84% Fair 14% and good 2%The prioritized solutions are conducting training for adolescents on anemia, KEK and stunting, forming youth groups